111 A systematic review exploring factors associated with palliative care utilisation in patients with Idiopathic Pulmonary Fibrosis. (14th March 2023) - Amin, Hamzah; Gatheral, Timothy; Gadoud, Amy; Khan, Aqib
Abstract : Background: Palliative care is being underutilised in patients with idiopathic pulmonary fibrosis (IPF). Barriers in accessing palliative care (PC) included prognostic uncertainty in IPF, lack of clarity regarding the role of PC and patients fear regarding the future. 1 The aim of this review is to explain how PC is currently being utilised in IPF patients. Methods: Medline and CINAHL were searched following a sensitive search strategy developed with a faculty librarian. Inclusion criteria included reporting PC utilisation in a health care setting as defined by WHO. 2 Results: From 245 search results, we included 12 articles. At a national and institutional level we found a PC utilisation of 0%-62% and 13.5%-36% respectively, with PC commencing 1 day – 1 month before death. PC was associated with in home and hospice death. PC utilisation did improve over time. Factors influencing PC utilisation include being older at the time of diagnosis with more severe comorbidities and residing closer to the institution. One cohort study highlighted patients receiving PC had more severe baseline disease which coincided with the centres focus on these measures. Many Cohort studies focused on the idea of a PC referral. Novel Education programmes, MDT approaches and decision aid tools all increased PC utilisation. Conclusion: PC utilisation has shown high variability, with onset of care too late to derive maximal benefit, however utilisation has been improving over time. Structured approaches taken by individual centres did improve PC utilisation, however, more research is needed to understand the upward trend in PC utilisation. While some studies focused on the idea of a PC referral, centres should be aware that PC can be delivered by a range of healthcare professionals. Novel models of PC delivery have paved the way forward in increasing PC utilisation, therefore, more research should focus on developing these approaches. References: Kim JW, Atkins C, Wilson AM. Barriers to specialist palliative care in interstitial lung disease: a systematic review. BMJ Support Palliat Care . 2019 Jun;9 (2):130–138. doi: 10.1136/bmjspcare-2018-001575. Epub 2018 Nov 21. PMID: 30464026. Who.int. 2022. Palliative care. [online] Available at: <https://www.who.int/news-room/fact-sheets/detail/palliative-care> [Accessed 19 August 2022].